Filtration-assisted magnetofluidic cartridge platform for HIV RNA detection from blood. Issue 5 (28th January 2022) - Trick, Alexander Y.; Ngo, Hoan Thanh; Nambiar, Anju H.; Morakis, Marisa M.; Chen, Fan-En; Chen, Liben; Hsieh, Kuangwen; Wang, Tza-Huei
Abstract : Blood plasma extraction using a 3D-printed filtration module coupled with magnetofluidic nucleic acid purification and quantitative PCR in a plastic cartridge enables a rapid, portable solution to screening and assessing HIV viral load. Abstract : The ability to detect and quantify HIV RNA in blood is essential to sensitive detection of infections and monitoring viremia throughout treatment. Current options for point-of-care HIV diagnosis ( i.e. lateral flow rapid tests) lack sensitivity for early detection and are unable to quantify viral load. HIV RNA diagnostics typically require extensive pre-processing of blood to isolate plasma and extract nucleic acids, in addition to expensive equipment for conducting nucleic acid amplification and fluorescence detection. Therefore, molecular HIV diagnostics is still mainly limited to clinical laboratories and there is an unmet need for high sensitivity point-of-care screening and at-home HIV viral load quantification. In this work, we outline a streamlined workflow for extraction of plasma from whole blood coupled with HIV RNA extraction and quantitative polymerase chain reaction (qPCR) in a portable magnetofluidic cartridge platform for use at the point-of-care. Viral particles were isolated from blood using manual filtration through a 3D-printed filter module in seconds followed by automated nucleic acid capture, purification, and transfer to qPCR using magnetic beads. Both nucleic acid extraction and qPCR were integrated within cartridges using compact instrumentation consisting of a motorized magnet arm, miniaturized thermocycler, and image-based fluorescence detection. We demonstrated detection down to 1000 copies of HIV viral particles from whole blood in <30 minutes.